Free‐form on every scale: "Tornado" roof structure for Bory Mall, Bratislava, Slovakia. Issue 3 (August 2016) - Helbig, Thorsten; Riederer, Jochen; Kamp, Florian; Oppe, Matthias
Abstract: The Bory Mall Shopping Centre, designed by the Italian architect Massimiliano Fuksas, is a mixed use development located on the outskirts of Bratislava, Slovakia. The roof to the shopping mall's central plaza is a free‐form steel gridshell. The concept for its shape is consistent from the footprint to the shape of the grid nodes. The gridshell is assembled from standard rolled steel hollow sections but uses the freedom created by individually shaped CNC‐milled grid nodes to achieve a smooth transition between high slenderness at the bottom and the necessary stiffness at the top. Working in close collaboration with Massimiliano Fuksas Architects, Knippers Helbig provided support for the development of the roof structure right from the start of the project and rounded off their services by providing detailed design of the free‐form central "Tornado" façade grid nodes, which were fabricated and built by Metal Yapi.